THE LINK BETWEEN FACE RECOGNITION TECHNOLOGY ADOPTION AND EMPLOYEE ENGAGEMENT: DOES JOB EVALUATION MATTER? - Nguyen, MinhTh-u T.; Pham, Chien V.; Nguyen, Khanh-Chi T.; Vu, Nam H. (International Journal of Application on Economics and Business, 2024)
Face recognition has been increasingly incorporated to workplaces to improve the workplace environment. It allows managers to identify workers hence efficiently manage human resource. This paper investigates the impact of four dimensions of face recognition (namely accuracy, time-saving, friendly interface, and data transparency) on employee engagement. The role of job evaluation in the relationship between face recognition and employee engagement is also examined. Using the probability sampling technique, a sample of 218 valid observations was gathered through the structured questionnaire survey in Vietnam, which is explored by correlation analysis and structural equation modelling. This study finds that face recognition significantly impacts employee emotional and moral engagement while having no effect on employees' continuance engagement. In addition, job evaluation has no moderating effect on the relationship between face recognition and emotional and continuance engagement, except for the link between face recognition and moral engagement. The results of this study demonstrate the vitality of face recognition in increasing employee engagement, incredibly in terms of emotion and morale. Face recognition is found to improve workplace fairness and confidence for employees. Meanwhile, information about working time helps employees self-assess their work progress and make adjustments to achieve goals at work. Finally, the interaction between job evaluation and face recognition increases moral engagement at the workplace, while it has no interaction with face recognition on emotional and maintaining engagement.